Role of the ortho-bridge system in the length unstable subtrochanteric femur fracture in school going children: a retrospective clinical study of 19 cases - Li, Mingjing; Xu, Jian; Xiang, Jiang; Zhu, Chunquan; Dai, Zonghui; Li, Fan (Frontiers in Pediatrics, 2023)
Background: Treating subtrochanteric femur fractures in pediatric patients remains challenging, and an optimal fixation device has yet to be established. This study aimed to asess the clinical and radiological outcomes of Ortho-Bridge System (OBS) treatment for length-unstable subtrochanteric femur fractures in children aged 5–16 years. Methods: We conducted a retrospective review of pediatric patients with subtrochanteric femur fractures treated with OBS between January 2018 and December 2021. The study included 19 children (12 boys, 7 girls) with an average age of 10.4±2.6 years. Two of the patients had pathological fractures associated with aneurysmal bone cyst. Demographic information, mechanism of accident, fracture type, associated neurovascular injuries, surgical duration and blood loss, were collected from the hospital database. Time to union and postoperative complications were recorded. Clinical and radiological outcomes were assessed using the Harris scoring system at the latest follow-up. Results: Injuries resulted from vehicle accidents in 10 patients (52.6%), falls over 3 meters in height in 3 patients (15.8%), and sports-related injuries in 6 patients (31.6%). The average patient weight was 41.5 kg (range: 21–78). Of the fractures, 14 (73.7%) were complex, and 5 (26.3%) were spiral. The average surgical duration was 111 minutes (range: 90–180), and the average surgical blood loss was 134mL (range: 70–300). The mean time to union was 12.7 weeks (range: 8–16). No cases of infection, malunion, implant failure, or femoral head osteonecrosis were reported. Leg length discrepancy of 10 mm was observed in one patient. All patients achieved excellent results according to the Harris scoring system. Conclusion: This study suggests that the OBS may serve as an effective alternative fixation option for managing length-unstable subtrochanteric femur fractures in school-aged children.